An unusual repressor controls the expression of a crucial nicotine‐degrading gene cluster in Pseudomonas putida S16. Issue 6 (20th February 2014) - Wang, Lijuan; Tang, Hongzhi; Yu, Hao; Yao, Yuxiang; Xu, Ping
Summary Transcriptional factors that contain helix–turn–helix (HTH) DNA‐binding domains are widespread in bacteria for regulating gene expression on demand, and function as homodimers that bind a palindromic DNA segment. Here, we show that an HTH‐containing transcriptional regulator, NicR2, in Pseudomonas putida S16 plays a critical role in controlling the expression of a crucial gene cluster (nic2) in nicotine degradation, and NicR2 binds DNA in a manner different from most other DNA‐binding proteins that use HTHs for recognition. Electrophoretic mobility shift assay (EMSA) and DNase I footprinting indicate that NicR2 directly interacts with a 28 bp inverted repeat (IR) in the nic2 promoter region. Using EMSA with synthetic DNA fragments, we found that both NicR2 dimer and tetramer can bind to the half‐site of the IR. This is confirmed independently by biolayer interferometry and cross‐linking experiments. Our results indicate that two NicR2 dimers bind to the IR cooperatively through protein–protein interactions, with each dimer binding the half‐site of the IR. Thus, NicR2 appears to be an unusual regulator, which uses HTH for recognition and displays the binding characteristics of some regulators that use β‐sheets. The transcriptional regulation of nicotine degradation in Pseudomonas highlights a new level of complexity in prokaryotic transcriptional regulation.